Dampak earning per share, debt to equity ratio, dan return on equity pada harga saham perusahaan: Studi empirik - Qurani, Ega Feprilia (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to explore the effect of earnings per share (EPS), debt to equity ratio (DER), and return on equity (ROA) on stock prices in wholesale and retail trade companies Tbk. The research method used is secondary data in the form of annual financial reports (Annual Report) from 2014 to 2016 published by the Indonesia Stock Exchange. The sampling technique used is purposive sampling with multiple linear regression analysis method. The results of the t-test prove that the value of EPS, DER, and ROE has a partially insignificant positive effect on stock prices. Meanwhile, the F (simultaneous) test of EPS, DER and ROE also has an insignificant positive effect on stock prices.